Етички размисли за изборниот фер-плеј и НВО-концептот како гласот на народот - Донев, Дејан (Konrad-Adenauer-Stiftung, Skopje, 2006)
The democracy is the best possible political and social ideology, orientation and political practice which means personal freedom and freedom of the people, equality between people, independence in theirs views for the society, freedom of living, acting and resolving all the questions and problems. The democracy expresses the faith in human reasonable ability to appoint the aims and ability to lead the society successful. That’s why today everybody tries to make reconstruction and development of the common life, of the great achievements, of human rights, of freedom on the individuals, of successful elections of the public representatives…, of the great achievement of our culture at all as a new form of free life according to the free mind. One of them is the idea for regular carried out elections of the public representatives, which in the next period will lead the state, but in the same time will show care for common life and good life. Here we speak about the concept of “fair play” in elections and ethical accent of respecting the people’s voice through which everybody express its rights and dignity as a member and participator in the society. We must have “game rules” so we can play it without fear that we’ll felt into empty space where the meaning of our choice will be lost. It is about one very important category of social moral that shows a high honesty, not cheating. From another angle, the biggest grants for this is the concept of NGO as a people’s, public voice. We have to provide participation on equal citizens in the process of determination. This will be the balance in the society, strenghting the democracy, and promotion on its true performing. If we want to have real, true leading of the society, we need a common government in which the citizen will be no longer only a user of the public policy, but will have some responsibilities in planning the policies, taking some activities and in evaluation of the policies. The modern citizens have the right to vote not only for the questions coming from their politicians, but also bringing propositions and initiating resolving of the questions of common life. The conclusion is that the democracy doesn’t mean election on every four or five years!
Ethical thoughts about election’s fair play and НГО concept as a voice of the people
Keywords: демократија, НВО, етика, избори